A review of basal ganglia circuits and physiology: Application to deep brain stimulation. (February 2019) - Eisinger, Robert S.; Cernera, Stephanie; Gittis, Aryn; Gunduz, Aysegul; Okun, Michael S.
Abstract: Introduction: Drawing on the seminal work of DeLong, Albin, and Young, we have now entered an era of basal ganglia neuromodulation. Understanding, re-evaluating, and leveraging the lessons learned from neuromodulation will be crucial to facilitate an increased and improved application of neuromodulation in human disease. Methods: We will focus on deep brain stimulation (DBS) – the most common form of basal ganglia neuromodulation – however, similar principles can apply to other neuromodulation modalities. We start with a brief review of DBS for Parkinson's disease, essential tremor, dystonia, and Tourette syndrome. We then review hallmark studies on basal ganglia circuits and electrophysiology resulting from decades of experience in neuromodulation. The organization and content of this paper follow Dr. Okun's Lecture from the 2018 Parkinsonism and Related Disorders World Congress. Results: Information gained from neuromodulation has led to an expansion of the basal ganglia rate model, an enhanced understanding of nuclei dynamics, an emerging focus on pathological oscillations, a revision of the tripartite division of the basal ganglia, and a redirected focus toward individualized symptom-specific stimulation. Though there have been many limitations of the basal ganglia "box model, " the construct provided the necessary foundation to advance the field. We now understand that information in the basal ganglia is encoded through complex neural responses that can be reliably measured and used to infer disease states for clinical translation. Conclusions: Our deepened understanding of basal ganglia physiology will drive new neuromodulation strategies such as adaptive DBS or cell-specific neuromodulation through the use of optogenetics.